2012
DOI: 10.3354/meps10013
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of long-term fertilization on salt marsh tidal creek benthic nutrient and N<sub>2 gas fluxes

Abstract: Salt marsh ecosystems serve as critical nutrient filters by removing reactive nitrogen (N) through denitrification. We examined the influence of long-term fertilization on N transformation and removal in a salt marsh tidal creek ecosystem fringing the Plum Island Sound estuary in northern Massachusetts, USA. Sediment oxygen demand was within the range of other marsh systems (1271.9 to 7855.0 µmol m −2 h −1) and was not significantly different between the fertilized and reference creek. Net N 2 fluxes ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 69 publications
4
23
0
Order By: Relevance
“…However, this relationship was driven entirely by N 2 O flux from the 323 treatment (5.83 6 3.6 lmolÁm À2 Áh À1 ), the same relationship from 0 through 163 was not significant indicating that the sediment community did not respond to nitrate additions until they were much larger than ambient levels. This is consistent with findings suggesting that DNRA may be outcompeting denitrification in nearby salt marsh tidal creeks that have been fertilized with nitrate (Vieillard and Fulweiler 2012). 2a, Table 2).…”
Section: Nutrient Addition Experimentssupporting
confidence: 90%
“…However, this relationship was driven entirely by N 2 O flux from the 323 treatment (5.83 6 3.6 lmolÁm À2 Áh À1 ), the same relationship from 0 through 163 was not significant indicating that the sediment community did not respond to nitrate additions until they were much larger than ambient levels. This is consistent with findings suggesting that DNRA may be outcompeting denitrification in nearby salt marsh tidal creeks that have been fertilized with nitrate (Vieillard and Fulweiler 2012). 2a, Table 2).…”
Section: Nutrient Addition Experimentssupporting
confidence: 90%
“…For this study, Deegan et al 2007 and Koop-Jakobsen and Giblin 2010, nitrate analysis as described in Methods. Vieillard and Fulweiler (2012) analyzed samples on a SEAL Autoanalyzer 3 instead of a Lachat Quik Chem 8000. points along each creek. These transects were at right angles to the creek channel axis and extended landward 50 m from the break between tall S. alterniflora and high marsh S. patens.…”
Section: Experimental Designmentioning
confidence: 99%
“…Recent studies indicate that N-fixation (reported as negative values, indicating sediment N 2 uptake) can be a significant N source in coastal sediments (−12 to −250 μmol N m −2 h −1 reported in: Fulweiler et al 2007;Mortazavi et al 2012;McCarthy et al 2015), reservoirs (approx. −200 μmol N m −2 h −1 ; Grantz et al 2012), and tidal flats (−402.7 μmol N m −2 h −1 ; Vieillard and Fulweiler 2012).…”
Section: Introductionmentioning
confidence: 99%